Biblia Qumranica. - Ego, Beate; Lange, Armin, 1961-; Lichtenberger, Hermann; De Troyer, Kristin (Brill, 2005)
The biblical Dead Sea Scrolls are about a thousand years older than the earliest complete manuscript of the Hebrew Bible and provide crucial insights into the history of the biblical texts. The Biblia Qumranica is the first comparative edition of these unique textual witnesses. The present volume provides a synopsis of the Minor Prophets manuscripts from Qumran and the other sites at the Dead Sea. In addition the Masoretic text (according to Codex Leningradiensis) and the Septuagint (according to the Göttingen edition) are included as reference texts. The Biblia Qumranica is a unique tool for text-critical analysis which allows for the first time to analyse and interpret the textual witnesses of the Hebrew Bible as preserved from the Second Temple period in comparison to each other.